Eksperimentasi Pembelajaran Kooperatif Tipe Stad dengan Pendekatan Open-Ended ditinjau dari Gaya Berpikir dan Kreativitas Siswa di Kabupaten Bojonegoro - nur rohman (Jurnal Penelitian Pendidikan, 2013)
This research used the quasi-experimental research method with the factorial design of 2 x 2 x 2. Its population was all of the students in Grade VIII of State Senior Secondary Schools in Bojonegoro in Academic Year 2013/2014. Based on the results of the data analyses, the conclusions were as follows. 1) STAD whit open-ended mathematic echievement better than STAD. 2) The students with the sequential thinking better mathematic achievement than with the random thinking. 3) The students high creativity mathematic achievement better than low creativity. 4(a) In the sequential thinking style, the STAD with the open-ended same mathematic achievement the STAD. (b) In the random thinking style, the STAD with the open-ended mathematic achievement better than STAD. 5(a) in the high creativity, the STAD with open-ended mathematic achievement better than STAD. (b) in the low creativity, the STAD with the open-ended in the same mathematic achievement STAD. 6(a) In the high creativity, the students with the sequential thinking style have a better mathematic achievement than those with the random thinking style; In the low creativity, the students with the sequential and random thinking style have the same mathematic achievement. (b) in the sequential thinking style, the students with the high creativity have a better mathematic achievement than those with the low creativity; and. In the random thinking style, the students with the high and low creativity the same mathematic achievement. 7) In the sequential thinking style with the high and the low creativity and in the random thinking style with the low creativity, the STAD with open-ended the same mathematic achievement the STAD, and in the random thinking style with the high creativity, the STAD with open-ended a better mathematic achievement than that the STAD